The effect of S-nitrosocaptopril and S-nitroso-N-acetyl-D,L- penicillamine on blood glucose concentration and haemodynamic parameters - Campbell, Sacha; Alexander-Lindo, Ruby; Dasgupta, Tara; McGrowder, Donovan (Journal of Applied Biomedicine, 2009)
Studies have shown that S-nitrosothiols (RSNOs) are able to affect glucose metabolism and blood pressure in animal models. This paper describes an investigation into the effect of two RSNOs, S-nitrosocaptopril (CapSNO) and S-nitroso-N-acetyl-D,L-penicillamine (SNAP) on fasting and postprandial blood glucose concentration, and systolic and diastolic blood pressures. Rats administered intravenously with CapSNO and SNAP, using dosages of 2.0, 5.0 and 12.5 mg/kg BW, showed a dose-dependent hyperglycaemic effect. Intravenous administration of 12.5 mg/kg BW of CapSNO and SNAP caused a statistically significant increase in fasting blood glucose concentration compared to rats treated with the same dosage of captopril. SNAP-treated rats showed a significantly greater elevation of fasting (F2) blood glucose concentration (5.91 ± 0.27 mmol/l) compared to CapSNO-treated rats (5.11 ± 0.08 mmol/l. However there was no significant difference in postprandial blood glucose concentrations. SNAP, CapSNO and captopril significantly reduced both systolic and diastolic blood pressures. This was accompanied by an increase in heart rate. The anti-hypertensive property of CapSNO and SNAP was more significant than that of captopril. CapSNO was more potent than SNAP in reducing blood pressure, suggesting that CapSNO may act via a combined mechanism that involves ACE inhibition and NO release.
Keywords: S-nitrosothioly; S-nitroso-N-acetylpenicilamin; experimenty na zvířatech; zvířata; Hemodynamics; Animals; kaptopril; Animal Experimentation; hemodynamika; Postprandial Period; potkani Wistar; S-Nitrosothiols; Captopril; krevní tlak; Rats, Wistar; Blood Glucose; Blood Pressure; krevní glukóza; Fasting; Statistics as Topic; Hyperglycemia; omezení příjmu potravy; S-Nitroso-N-Acetylpenicillamine; hyperglykemie; postprandiální období; statistika jako téma